Occurrence of urinary schistosomiasis and associated bacteria in parts of Ondo State, Nigeria - Kikelomo J. Kone; Anthony K. Onifade; Ebenezer O. Dada (Public Library of Science (PLoS), 2022)
Schistosomiasis is a parasitic disease caused by blood flukes (trematode worms) of the genus Schistosoma and is common among the rural community dwellers that have occupation or recreation activities that link them with infected water bodies. The disease wreak a lot of havoc in the victims which range from anaemia, increase risk of liver fibrosis and bladder cancer, enlarged liver, difficult and painful urination, infertility etc. Nigeria has been reported to be the most endemic country in the world for schistosomiasis with about 29 million infected cases. However, people with urinary schistosomiasis are vulnerable to secondary infections caused by bacteria as a result of the break down in the mucosa barrier occasioned by the wear and tear of the spiny eggs of the schistosomes. Meanwhile, the control measures instituted by various agencies against schistosomiasis paid little attention to its co-infection with bacteria. This study was designed to evaluate the occurrence of urinary schistosomiasis and co-infection with bacteria in parts of Ondo State, Nigeria. Ethical approval was obtained from the Ethical Committee of the Ondo State Ministry of Health, Akure. Macroscopic and microscopic examinations, and microbiological analysis of the urine samples collected were performed using standard techniques. Of the five hundred and nine (509) urine collected, ova of Schistosoma haematobium were detected in one hundred and twenty one 121 (23.77%), significant bacteriuria was detected in 104 (20.43%) and co-infection was detected in thirty six 36 (29.75%) of schistosomiasis cases. There was a positive association between urinary schistosomiasis and bacteriuria (X2(1) = 8.481, p = 0.004). This study revealed a high occurrence of urinary schistosomiasis and significant bacteriuria in the study areas which suggests that bacterial presence may be a potent complication in the management of urinary schistosomiasis.